The results of the index comparative evaluation of photodynamic therapy and ultraviolet irradiation in the treatment of chronic gingivitis - K. V. Losev; T. V. Kostyakova; N. V. Batsula; M. A. Verendeeva; O. V. Kuzina; A. V. Losev (Biomedical Photonics)
In this clinical study, the effect of photodynamic therapy and ultraviolet radiation on the effectiveness of the treatment of periodontal diseases was examined according to the results of an index assessment. Clinical examination of 95 patients of both sexes aged from 18 to 32 years revealed chronic generalized catarrhal gingivitis (K05.1). The main index criteria for comparative parameters in all study groups were: simplified OHI-S hygiene index, Mullemann-Cowell bleeding index, PMA index. The indices were measured before and after treatment with subsequent control examinations in 1 month, 3 months, 6 months. The patients were divided into three groups and each group underwent standard periodontal treatment aimed at stopping the inflammatory process and preventing its further development. In the first group, the treatment was supplemented with the use of the FotoSan LED lamp with a wavelength of 630 nm, in the second the “Quasar” ultraviolet irradiator was used, in the third (control) group, the complex of therapeutic measures was carried out without physiotherapeutic procedures. According to the results of the study, the use of photodynamic therapy significantly accelerates the regenerative processes of periodontal epithelial tissue and reduces the number of treatment sessions.